Bioavailable heavy metal concentration in classroom dust and related health risk assessment of primary school children in Rawang, Malaysia - Tan, Sock Yin (2020)
Children are vulnerable to heavy metals in classroom dust. A total of 51 classroom dust samples were collected from children’s palms using wet tissue wiping method from April to June 2016. Physiologically Based Extraction Test (PBET) was applied to determine bioavailable heavy metal concentrations and potential health risks among the school children were estimated. The highest mean of bioavailable heavy metal concentration in classroom dust was Zn (12.5103 μg/g), followed by Cu (0.9585 μg/g), Ni (0.5340 μg/g), Cr (0.0472 μg/g), Co (0.0234 μg/g), As (0.0177 μg/g), Cd (0.0096 μg g), and Pb (0.0050 μg/g). Principal Component Analysis (PCA) was used to determine heavy metal sources in classroom dust. Heavy metals in PC1 (As, Cd, Co, Cu, Zn) were mostly linked with natural and anthropogenic sources, while PC2 (Cr, Ni) were more related to anthropogenic activities (industrial activities, traffic congestion). Hierarchical cluster has indicated three clusters, namely Cluster 1 (S3, S4, S6, S15) as residential areas, Cluster 2 (S7, S9, S10, S12) as industrial area and Cluster 3 (S1, S2, S5, S8, S14, S11, S13, S16, S17) as a mixed land use area (residential, industrial, plantation). Emissions from vehicles, plantations and industrial activities were the main heavy metal sources in classroom dust. The relationship between bioavailable heavy metal concentrations in classroom dust with school and classroom characteristics was done using Spearman’s Rho. Only Cu (r = 0.767, p = 0.016) was found significant related with distance between school and traffic road, while Cd (r = -0.725, p = 0.027) was found negatively related to classroom floor level. There were no potential health risks (non-carcinogenic and carcinogenic) of ingestion pathway reported.